Праслов’янська антропонімна спадщина в Реєстрі Війська Запорозького Низового 1756 року - Дзира, І. (Сiверянський лiтопис, 2018)
У статті проаналізовано етимологічний склад, сортимент і частоту вживання
слов’янських автохтонних імен і похідних від них прізвищевих назв, які представлені в
Реєстрі Війська Запорозького Низового 1756 р. Зроблено висновок, що, незважаючи на
тенденцію до майже повного зникнення, праслов’янські імена продовжували існувати в
українській антропонімній системі ХVІІІ ст. у вигляді прізвищевих назв. В статье проанализированы этимологический состав, сортимент и частота употребления славянских автохтонных имён и производных от них фамильных названий,
представленных в Реестре Войска Запорожского Низового 1756 г. Сделан вывод, что, несмотря на тенденцию к почти полному исчезновению, праславянские имена продолжали
существовать в украинской антропонимной системе ХVIII в. в виде фамильных названий. The article deals with analysis of the etymological staff, assortment and frequency of the
Slav autochthonic names and derivative from their family names, listed in the 1756 Register
of the Zaporozhian Host. Since from the whole quantity of the Slav autochtonic names in
the Ukrainian language XVIII cen. continued functioning only those which were legalized by
church, the antroponims Радко and Ярош, which are available in the source, it is valid to
regard them not as evidence of existence of the remains of the original Slav anthroponimic
heritage, but as consequence of the change of morphological structure of the Christian names
Родионъ and Иеремия or Єрофей. The family names, which are formed from the Slav
personal names-composites, happen in register very seldom. The register contains twenty four
denominations which originate from original Slav names fromcomposite origin. Taking into
account the circumstances of the rise and functioning of family names in New Sich, and also
taking into account eye-witness evidences about motives of the choice, it is possible to affirm
absence of direct genetic connection between Zaporozhian nicknames formed from vocabulary
«nomina impersonalia», and original Slave names. Primary dependence can only be affirmed
about those family names of the type «nomina personalia», the stem of which reflected in the
parents attitude to the childbirth, aspiration to save its life, perhaps, the sequence of the birth.
The results of the study have shown, that despite of the tendency to almost total disappearance,
the original Slav names continued to exist in Ukrainian anthroponimic system in the XVIII cen.
as the family names.